Car Age, Taxation, Scrappage Premiums and the ELV Directive - F. Mikael Sandström (The Research Institute of Industrial Economics (IUI), 2003)
A chain of replacement model is used to examine the effects of automobile taxes and of a scrappage premium on the life length of cars, and on the size of the car fleet. The predictions of the model are tested on data on the scrappage of cars in Sweden 1989-2002. The theoretical model predicts that increased taxes on the purchase of cars should increase the life length of cars, and reduce the number of cars. A scrappage premium would have the opposite effects. Changes in periodic taxes would have no effects on the life length of automobiles, but would reduce the size of the car stock. The econometric analysis indicates, however, that the effects both on the life-length of cars, and on the size of the car parc are small. On the basis of the conclusions from the theoretical and the empirical analysis, the possible implications of the European Union's Directive 2000/53/EC on end-of life vehicles (ELV) are discussed.
Keywords: H29; L62; Q48; 330; Taxes; Automobiles; Accelerated Vehicle Retirement Programs; Scrappage; ELV Directive; Schrott; Kraftfahrzeug; EU-Recht